Kestly Miller: capstone - Miller, Kestly, artist (Colorado State University. Libraries, 2015)
The artist's statement: I am a seeker. I am interested in the small moments that reflect my awe and appreciation of the natural world. With a background and interest in science, I am always curious; searching, exploring and seeing things like a child with fresh eyes and appreciation for the detail. By dissecting and investigating the world around me, I want to capture the timeless elegance of the micro and the macro. This approach of discovery and understanding are practices I share with both artists and scientists alike. Profoundly strange and beautiful ideas offered through concepts like quantum physics and properties of the elements find a visual presence throughout my work. My goal is to express the raw emotion experienced in these small, often overlooked, moments. I want others to consider the role visual art plays within the translation of scientific information. The lessons I have learned through the study of science never felt truly real or applicable until I applied them to the visual language. By utilizing tools used to experiment, document and investigate, a visual representation can move beyond that which only our eyes and hands can identify. The process, use of materials and fieldwork are as important than the final piece itself. Much of these concepts derived from the ideas of time and place. Everything is constantly moving and evolving. Painting is a path of self-exploration and understanding. The investigation and exploration aspects will continually keep me seeking, knowing that I will never have all of the answers. By making my experiences and processes visual, they become a physical object that others can then respond to, facilitating a dialog. In the end, I believe this creativity is my strongest desire to connect the self with the infinite possibilities of the imagination.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.